2021
DOI: 10.1371/journal.pone.0248798
|View full text |Cite
|
Sign up to set email alerts
|

Co-culture of type I and type II pneumocytes as a model of alveolar epithelium

Abstract: The epithelial tissues of the distal lung are continuously exposed to inhaled air, and are of research interest in studying respiratory exposure to both hazardous and therapeutic materials. Pharmaco-toxicological research depends on the development of sophisticated models of the alveolar epithelium, which better represent the different cell types present in the native lung and interactions between them. We developed an air-liquid interface (ALI) model of the alveolar epithelium which incorporates cell lines wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
2
12
0
1
Order By: Relevance
“…[50,95] Similarly, multilayer formation by the polyclonal cell line hAELVi was demonstrated in our study supporting the findings of others. [50,96,97] The single-cell clone "Arlo," however, demonstrated the formation of a polarized monolayer in a direct comparison with the polyclonal hAELVi cell line under equal culture conditions. The evaluation of the tissue morphology, which is based on quantitative image analysis, demonstrates that the monolayer morphology of "Arlo" is not limited to certain areas within selected sections-it represents the dominant tissue architecture.…”
Section: Figuresupporting
confidence: 92%
See 3 more Smart Citations
“…[50,95] Similarly, multilayer formation by the polyclonal cell line hAELVi was demonstrated in our study supporting the findings of others. [50,96,97] The single-cell clone "Arlo," however, demonstrated the formation of a polarized monolayer in a direct comparison with the polyclonal hAELVi cell line under equal culture conditions. The evaluation of the tissue morphology, which is based on quantitative image analysis, demonstrates that the monolayer morphology of "Arlo" is not limited to certain areas within selected sections-it represents the dominant tissue architecture.…”
Section: Figuresupporting
confidence: 92%
“…Another study looked at culture times of 30 d, but only reported maximum TEER values of ≈140 Ω cm 2 at day 10 of culture for NCI-H441 cultured under ALI conditions, which also declined rapidly after this maximum. [50] In addition, multilayer formation was reported for NCI-H441 in several studies, further complicating the assessment of TEER development when no quantitative assessment of multilayer formation is performed in parallel. [50,95] Similarly, multilayer formation by the polyclonal cell line hAELVi was demonstrated in our study supporting the findings of others.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, unlike airway epithelial cells, a consistent method to passage and expand primary ATII cells under 2D conditions has not yet been established. A few studies have investigated the culture of alveolar epithelial cell lines (such as A549 and NCI-H441) or inducible pluripotent stem cells (iPSC)-derived ATII cells under ALI, showing increased cell polarization, barrier formation, ion transport, and cell maturation [ 38 , 39 , 40 ]. However, none of these models supports both the maintenance of the ATII phenotype and the differentiation into ATI cells.…”
Section: Lung 3d Culturesmentioning
confidence: 99%